Cabaret plays by Petr Potemkin - Брызгалова, Елена (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2011)
This article discusses studies of some works by Petr P. Potemkin, a poet and playwright of the Silver Age. His plays for revue theatres and cabarets have not been studied yet, and the author of the article suggests her understanding of this part of Potemkin’s artistic legacy. The article studies specific features of the one-act drama of the early 20th century.